2014
DOI: 10.1007/s00227-014-2573-9
|View full text |Cite
|
Sign up to set email alerts
|

Gut evacuation rate and grazing impact of the krill Thysanoessa raschii and T. inermis

Abstract: Gut evacuation rates and ingestion rates were measured for the krill Thysanoessa raschii and T. inermis in Godthåbsfjord, SW Greenland. Combined with biomass of the krill community, the grazing potential on phytoplankton along the fjord was estimated. Gut evacuation rates were 3.9 and 2.3 h −1 for T. raschii and T. inermis, respectively. Ingestion rates were 12.2 ± 7.5 µg C mg C −1 day −1 (n = 4) for T. inermis and 4.9 ± 3.2 µg C mg C −1 day −1 (n = 4) for T. raschii, corresponding to daily rations of 1.2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…The depth‐integrated zooplankton biomass recorded during the same spatial survey (data already reported in Teglhus et al . []; reproduced in Figure ) exhibited a similar spatial pattern, with a peak in krill biomass around GF10 (0.38 g C m −2 ) and maximum in copepod biomass around GF7 (0.84 g C m −2 ) .…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…The depth‐integrated zooplankton biomass recorded during the same spatial survey (data already reported in Teglhus et al . []; reproduced in Figure ) exhibited a similar spatial pattern, with a peak in krill biomass around GF10 (0.38 g C m −2 ) and maximum in copepod biomass around GF7 (0.84 g C m −2 ) .…”
Section: Resultsmentioning
confidence: 61%
“…As stratification and light climate conditions are comparable between stations (Table ), a difference in grazing pressure by zooplankton could be an explanation for the absence of a spring bloom in April–May near the glacier front. Data on zooplankton biomass and grazing experiments however show that the grazing impact is low (maximum 15% of phytoplankton community, [ Teglhus , ]), suggesting that physical drivers must play a dominant role. So why did the spring bloom not develop close to glacier, i.e., at station GF17?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high biomass contribution of Metridia longa at the subsurface front implies that local conditions favour its growth. This finding is in line with zooplankton community observations in Nuup Kangerlua that follow the outflow of subglacial water from the inner fjord tidewater glacier towards the mouth (Tang et al, 2011;Swalethorp et al, 2015;Teglhus et al, 2015). Each of these case studies reported a peak in the biomass of M. longa in the same area as the front associated with the subglacial water mass, from ∼0.75 g C m -2 in May to ∼2.5 g C m -2 in August.…”
Section: Aggregation Of Zooplanktonsupporting
confidence: 87%
“…They have the same grazing potential as copepods (Teglhus et al 2015), thereby forming a major link between primary producers and marine vertebrate predators, including fish, birds and mammals (Mauchline & Fischer 1969, Astthorsson & Gislason 1997, Rosing-Asvid et al 2013. It is crucial to understand the environmental drivers of krill population dynamics to predict how future changes in marine environments will affect plankton communities.…”
Section: Introductionmentioning
confidence: 99%